Idiopathic Sudden Sensorineural Hearing Loss Is Not a Sentinel Event for Acute Myocardial Infarction. Issue 7 (August 2018) - Crowson, Matthew G.; Mulder, Hillary; Cyr, Derek D.; Langman, Alan W.; Lee, Walter T.; Parham, Kourosh; Pynnonen, Melissa A.; Schulz, Kristine; Shin, Jennifer J.; Witsell, David; Vambutas, Andrea
Abstract : Objective: Given ongoing debate about the suggested association, the primary objective was to determine if idiopathic sudden sensorineural hearing loss (ISSNHL) was a sentinel event for acute myocardial infarction (AMI) in adults. Study Design: Case-control study. Setting: United States MarketScan administrative health claims database. Patients: Aged 18 years or older, had a diagnosis of ISSNHL on or after January 1st, 2011 and had sufficient follow-up data available to assess for AMI occurrence. Intervention: N/A. Main Outcome Measures: Incidence rates (per 1, 000 patient years) of AMI for cases and controls were computed. Adjusted and unadjusted Cox proportional hazards models were created to explore possible associations between ISSNHL and initial AMI. Results: A total of 10, 749 ISSNHL cases and 10, 749 matched controls were included. There were no significant differences in the incidence rate of AMI between ISSNHL cases (8.29 events/1, 000 person-years) and controls (9.25 events/1, 000 person-years), nor were there differences within age groups, sex, or comorbidity status (overall incidence rate ratio 0.90; 95% confidence interval [CI] 0.70–1.15 p  = 0.39). The unadjusted and adjusted Cox proportional hazards models did not demonstrate an association between ISSNHL and initial AMI (hazard ratio [HR]: 0.90, 95% CI: 0.70–1.15; HR: 0.86, 95% CI: 0.67–1.10, respectively). Conclusions: ISSNHL is not a predictor of an initial AMI in adult patients from the United States. Considerable inconsistencies in associations between cardiovascular risk factors and ISSNHL exist in the literature. Further work is needed to confirm or refute direct associations between cardiovascular disease risk factors and ISSNHL before definitive mechanistic conclusions can be made. Abstract : Supplemental Digital Content is available in the text